Quality assurances practices, training needs and international students mobility: analysing the nexuses - Abbo, Usman; Bashir, Adamu (Universiti Utara Malaysia, 2016)
The role of education’s quality in determining international students’ choice of study destination was discussed by several studies. However, it only seems to have gained a huge prominence recently by constituting a theme in the quality management field involving empirical studies.In spite of such prominence the theme does not seems to provide sufficient empirical evidence forging a nexus between quality assurance practices, training needs and international student’s mobility.This research work therefore attempts to fill this gap by examining how the search for quality education and training needs satisfaction play role in international student’s mobility. Six dimensions of quality assurance in education were identified through extensive literature reviewed, three dimensions of training needs were equally revealed by the literature. Nine hypotheses were thus developed using these dimensions with the view to explain the relationship among the variables involved. The primary data for this study was obtained through a cross-sectional survey of International students in University Utara Malaysia with the aid of questionnaires, where a total of 150 respondents were selected randomly.Partial Least Squares (PLS) method was adopted in analysing the collected data with smartPLS 2.0 to determine the relationship involved.The result supported the relationship between organizational needs, Tangibility of facilities, Nature of service delivery and international student’s mobility, while the other six relationships were not supported.